СИСТЕМА ДИСТАНЦІЙНОГО МОНІТОРИНГУ СТАНУ ВИСОКОВОЛЬТНОЇ КАБЕЛЬНОЇ ЛІНІЇ - Щерба, А.А.; Подольцев, О.Д.; Кучерява, І.М. (Інститут електродинаміки Національної академії наук України, 2020)
The article proposes a device for remote monitoring of high-voltage cable line state. The device gives a possibility to measure simultaneously several diagnostic characteristics, i.e. the temperature of cable outer sheath, electric current in cable core, capacitive current to earth and uses a specially designed internal electric power source that directly converts the energy of cable electromagnetic field into electric energy with necessary parameters. By computer simulation, the temperature field distribution in the cable cores of 330 kV cable line is determined and the quantitative relationship between the directly measured temperature on the cable outer sheath and the temperature values of the cable core and insulation, which are important diagnostic characteristics of the thermal state of power cables is revealed. Ref. 5, fig. 3.